THE PHYSICAL FITNESS OF A GROUP OF ELDERLY WOMEN (Fiep Bulletin - online, 2014)
Nowadays, the ageing population is a widespread phenomenon. In Brazil, it stands at about 15 million and on current projections there will be about 34 million in 2025. According to the Activity Theory, the elderly must keep themselves active, participant and integrated to the society in order to  maintain their quality of life. The physical activity is extremely important to guarantee longevity with quality, so it is essential to lead a healthy style of life. This article results from a research conducted in order to analyse the physical fitness of 30 elderly women, between the ages of 60 and 74, who took part in a structured program of physical activity in the Support Center of the Elderly Attention Department, in Palmeira - PR. The research results were obtained through the following tests: sitting down and standing up for 30 seconds test  and the 6-minutes walk test, described by Rikli and Jones, (1999) and mentioned by Matsudo, (2004), and the static balance test, which is part of the battery of tests described by  Williams and Greene, (1990) and mentioned by Spirduso, (1995). The results achieved were: in the sitting down and standing up for 30 seconds test the pre-test showed an average of 12, 9 repetitions to 19,3 repetitions in the post-test; in the 6-minutes walk test the average was 516,07 meters in the pre-test and 579,45 meters in the post-test; in the static balance test it was  18,1 seconds in the pre-test and 30 seconds in the post-test. It was used the T-Student criterion, with a level of significance of 5%, in which the differences were statistically significant in all variables, being of  p
Keywords: elderly women; physical fitness; physical activity; gerontology